The impact of bolsonarismo on COVID-19 vaccination coverage in Brazilian municipalities - Vitor de Moraes Peixoto; João Gabriel Ribeiro Pessanha Leal; Larissa Martins Marques (Centro Brasileiro de Estudos de Saúde, 2023)
ABSTRACT The immunization campaign against COVID-19 started in Brazil in January 2021 after strong pressure from society on the federal government, which had created a series of ideological obstacles against vaccines, especially those produced with Chinese inputs. This article analyzes the impact of far-right ideology on the spatial distribution of vaccine coverage against COVID-19 in Brazilian municipalities. By means of hierarchical models, it was identified that, maintaining constant socio-demographic characteristics and the structures of the Unified Health System, the degree of bolsonarismo in the municipalities had a negative impact on the coverage rates of the first, second and, especially, of the third dose.